2020
DOI: 10.1002/mbo3.984
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the core microbiome in tobacco leaves during aging

Abstract: Microbiome plays an important role during the tobacco aging process which was an indispensable link in the production and processing of cigarettes. However, the structure and functions of microbiome have not been clarified during the tobacco aging process. In this study, 16S rDNA and ITS amplicon sequencing techniques were used to analyze the core microbiome of 15 tobacco samples from five different aging stages. The whole bacterial microbiome was classified into 29 microbial phyla and 132 orders. Enterobacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 49 publications
4
30
0
Order By: Relevance
“…Cigar tobacco is air-cured; however, cured but unfermented tobacco is not suitable for cigar products because of its sharp and pungent flavor (Zhao et al, 2007). Artificial fermentation is a more control- After 24 months of natural aging, the content of WSS decreased by 2.63%, whereas the contents of TN, nicotine, starch, and protein decreased slightly (Zhou et al, 2020). Conversely, the contents of chemical components decreased significantly after short-term artificial fermentation (Qiu et al, 2003), consistent with the findings of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Cigar tobacco is air-cured; however, cured but unfermented tobacco is not suitable for cigar products because of its sharp and pungent flavor (Zhao et al, 2007). Artificial fermentation is a more control- After 24 months of natural aging, the content of WSS decreased by 2.63%, whereas the contents of TN, nicotine, starch, and protein decreased slightly (Zhou et al, 2020). Conversely, the contents of chemical components decreased significantly after short-term artificial fermentation (Qiu et al, 2003), consistent with the findings of this study.…”
Section: Discussionmentioning
confidence: 99%
“…® Soil DNA Kit (Omega Bio-tek), and the concentration and purity of DNA were assessed by electrophoresis on 1.0% weight/volume agarose gels. The primers used to amplify the V4 variable region of the bacterial 16s RNA gene were: 515F (5′-GTGCCAGCMGCCGCGGTAA-3′) and 806R (5′-GGACTACHVGGGTWTCTAAT-3′) ( Zhou et al, 2020 ). DNA amplification was carried out using the ABI GeneAmp 9700 polymerase chain reaction (PCR) instrument.…”
Section: Methodsmentioning
confidence: 99%
“…among the culturable endophytic bacteria isolated from tobacco leaves has been previously described by Chen et al [ 6 ]. Such cultivation-based endophytic bacteria isolation does not reflect the complexity of the tobacco bacterial endophytome revealed by metagenomic analysis [ 5 ]. It is likely that the limits of cultivation-based isolation are set by the inability of unculturable bacteria to grow on artificial media in combination with the harsh treatment required for leaf surface sterilization, which likely leads to the excessive disinfection of microorganisms residing in soft tobacco leaf tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Sequencing-based analysis revealed that endophytic Enterobacteriaceae communities predominately colonize tobacco seeds with varied abundance among the distinct cultivars; meanwhile, a genotype-specific signature was mainly observed among Alpha-proteobacteria [ 4 ]. Enterobacteriaceae was also shown to dominate the bacterial community of fresh tobacco leaves, and in terms of abundance it is followed by Pseudomonadaceae, Sphingomonadaceae, Xanthomonadaceae, Moraxellaceae, Bacillaceae, Comamonadaceae and Methylobacteriaceae [ 5 ]. Bacillus spp., such as B. pumilus , B. amyloliquefaciens , B. cereus , B. subtilis , B. flexus , B. simplex and B. megaterium , were dominant among the 11 species isolated from tobacco leaves using a cultivation-based approach [ 6 ].…”
Section: Introductionmentioning
confidence: 99%